2019
DOI: 10.1111/jnu.12504
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of PhD Dissertation Research by Dissertation Format: A Retrospective Cohort Study

Abstract: Purpose The study purpose was to compare dissemination of PhD dissertation research by dissertation format: traditional (five‐chapter document providing a complete and systematic account of the PhD research) versus an alternate (substudy [document containing three smaller studies but not written as stand‐alone manuscripts] or publication [document containing three or more related manuscripts intended for submission or published in a peer‐reviewed journal]) format. Design A retrospective study of all PhD disser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Medical specialist are expected to lead multi-professional healthcare teams, be experts in their elds, and be able to assimilate pertinent medical knowledge and critically assess emerging ndings in the literature as such, they must possess a level of familiarity with the medical literature that can only be attained by conducting research and publishing papers themselves, (28). The dissemination of research through peer-reviewed publications is critical for the profession and the professional development of the upcoming medical scientist (29).…”
Section: Disseminating Dissertation Research Resultsmentioning
confidence: 99%
“…Medical specialist are expected to lead multi-professional healthcare teams, be experts in their elds, and be able to assimilate pertinent medical knowledge and critically assess emerging ndings in the literature as such, they must possess a level of familiarity with the medical literature that can only be attained by conducting research and publishing papers themselves, (28). The dissemination of research through peer-reviewed publications is critical for the profession and the professional development of the upcoming medical scientist (29).…”
Section: Disseminating Dissertation Research Resultsmentioning
confidence: 99%
“…It is a well-known fact that unpublished findings from a PhD theses are a lost opportunity for both the candidate and the scientific community because research findings reported in thesis are less likely to be cited in academic journals, especially if the thesis is not written in English (4). This is an important reason why both candidates and supervisors would like to publish the results before the PhD thesis is submitted and defended.…”
Section: The Importance Of Publishing Journal Articles Based On the T...mentioning
confidence: 99%
“…This book focuses on doctorates of this format, which is the most common in the social sciences. However, there is no evidence suggesting that the quality of research undertaken or the training given to new researchers needs to vary because of the precise format of their doctoral studies (Evans et al, 2018;Smaldone et al, 2019). The key to all doctorates, this highest qualification, is generally thought to be the quality of research they report.…”
Section: What Is a Doctoral Degree?mentioning
confidence: 99%